2009
DOI: 10.1099/vir.0.004580-0
|View full text |Cite
|
Sign up to set email alerts
|

Variants of open reading frame Bm126 in wild-type Bombyx mori nucleopolyhedrovirus isolates exhibit functional differences

Abstract: The open reading frame (ORF) 126 (Bm126) of Bombyx mori nucleopolyhedrovirus (BmNPV) is a homologue of Ac150 and belongs to the baculovirus 11K protein family. Bm126 was amplified from BmNPVs isolated from five different regions of China. Sequence analysis showed that the isolates had two different subtypes of Bm126, Bm126-SX and Bm126-GD, and both were different from that of the BmNPV T3 isolate. All of the BM126 ORFs contained a hydrophobic N terminus and a C6 motif at their C terminus, but the sequence betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Deletion mutants of two of the Ac150 subtypes exhibited an increase in survival time, but not a decrease in oral infectivity in agreement with the first study (Hao et al, 2009).…”
Section: Ac145 (11k Protein)supporting
confidence: 89%
See 4 more Smart Citations
“…Deletion mutants of two of the Ac150 subtypes exhibited an increase in survival time, but not a decrease in oral infectivity in agreement with the first study (Hao et al, 2009).…”
Section: Ac145 (11k Protein)supporting
confidence: 89%
“…Both scenarios have been documented in the literature (Cory and Myers, 2003), and are a key element in the virulence of baculovirus populations in the field. There is also evidence to suggest that mixtures of wildtype and pif knockout polyhedra produce a more virulent population than the wild type alone (Hao et al, 2009 -pif-0, pif-1, pif-2, and pif-3 found that mixtures of these viruses were also noninfectious to the host per os . This result suggests that virus infection requires all four of these PIFs present on the same ODV, and is not unexpected given their conservation across all baculoviruses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations